2014
DOI: 10.1371/journal.pone.0105543
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Influenza and RSV among Inpatients and Outpatients in Rural Western Kenya, 2009–2012

Abstract: BackgroundIn Kenya, detailed data on the age-specific burden of influenza and RSV are essential to inform use of limited vaccination and treatment resources.MethodsWe analyzed surveillance data from August 2009 to July 2012 for hospitalized severe acute respiratory illness (SARI) and outpatient influenza-like illness (ILI) at two health facilities in western Kenya to estimate the burden of influenza and respiratory syncytial virus (RSV). Incidence rates were estimated by dividing the number of cases with labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
111
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(129 citation statements)
references
References 31 publications
13
111
5
Order By: Relevance
“…We found substantially higher rates of influenza-associated SARI among 19-59 years old cases (57.8 ) and lower rates in cases < 5 years old (8.3 ) or > 60 years old (9.3 ) ( Table 4). This finding is inconsistent with observations in temperate countries, where the highest influenza-associated hospitalization was observed for infants aged < 5 years and in persons aged > 65 years (23,30,32,33). This may be because the median age of the Vietnamese population is 25 years, and 61.4 of the population is 15-64 years of age (34); further, social contact related to the spread of infectious disease between individuals is greatest for adults aged 40-60 years in Vietnam (35).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found substantially higher rates of influenza-associated SARI among 19-59 years old cases (57.8 ) and lower rates in cases < 5 years old (8.3 ) or > 60 years old (9.3 ) ( Table 4). This finding is inconsistent with observations in temperate countries, where the highest influenza-associated hospitalization was observed for infants aged < 5 years and in persons aged > 65 years (23,30,32,33). This may be because the median age of the Vietnamese population is 25 years, and 61.4 of the population is 15-64 years of age (34); further, social contact related to the spread of infectious disease between individuals is greatest for adults aged 40-60 years in Vietnam (35).…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings are similar to those of other reports of the viral etiologies associated with SARI from Asia and other countries (12,(17)(18)(19)(20)(21)(22). Many studies from both temperate and tropical countries have described the epidemiology and outcome of influenza A H1pdm09 associated with hospitalized SARI (12,17,(23)(24)(25)(26). Influenza infection is well-recognized as the cause of significant healthcare costs, morbidity, and mortality in temperate countries (27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, overall, 19% of SARI cases of all age groups were influenza positive. Although the influenza positivity among SARI cases was reported to be 8% in Oman, (4) and 9% in Jordan (18), both in the Eastern Mediterranean Region of WHO, the influenza positivity among SARI cases in Asia and Africa found in other studies (5,9,17,(19)(20)(21) ranged between 8-11%. The reasons why we found a higher percentage of influenza positivity amongst SARI cases could be attributed to the fact that we sampled 93% of all SARI cases that met the WHO case definition for SARI while in all those countries where a low (18).…”
Section: Influenza Incidencementioning
confidence: 86%
“…For example, in a report of sentinel surveillance data of ILI or severe ARI (SARI) from 15 African countries from 2006–2010, children under the age of 5 accounted for 48% of all the ILI and SARI cases (113,164 cases), and 10% of these SARI cases tested positive for influenza [94]. On a country-specific level, investigators in several epidemiologic studies conducted in different regions in Kenya found that infants under age 1 had among the highest rates of influenza-associated SARI [95,96] or medically-attended lower respiratory tract infection [97] of all pediatric age groups, similar to developed countries. In South Africa, both HIV-infected and uninfected infants under 1 year of age were estimated in one analysis to have the highest rates of pneumonia and influenza deaths [98].…”
Section: Burden Of Influenza In Young Infantsmentioning
confidence: 99%